The sociology of citizenship within socio-cultural contexts: a reinterpretation of identity and civic participation - Ramadhan, Iwan; Dewantara, Jagad Aditya (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
This editorial concludes with a call to academics, researchers, and education practitioners to develop a sociology of citizenship rooted in Indonesia"™s socio-cultural realities. By understanding citizenship as a living, dynamic, and multivocal construct, we can formulate more inclusive, just, and context-sensitive educational and policy strategies. Interdisciplinary collaboration among sociology, anthropology, education, and law is essential to produce comprehensive and solution-oriented insights. Only by viewing citizens as active subjects in social life, rather than mere objects of state policy, can we build a future of Indonesian citizenship that is dignified, socio-culturally grounded, and inclusive.